Assessment of effect of intravitreal ranibizumab injection on the ocular blood flow in patients with neovascular age-related macular degeneration - V. V. Neroev; T. N. Kiseleva; M. V. Ryabina; L. V. Karapetyan; K. A. Ramazanova (Oftalʹmologiâ, 2014)
Purpose: To evaluate the effect of intravitreal ranibizumab injection on the ocular blood flow in patients with neovascular agerelatedmacular degeneration (AMD).Methods: 35 patients with wet AMD undergone intravitreal 0.5 mg ranibizumab injection. Color Doppler Imaging (CDI) and dopplerographywere used to measure hemodynamic parameters including the peak systolic velocity (Vsyst, cm / s), end-diastolic velocity (V diast, cm / s), and resistance index (RI) of blood flow in the central retinal artery (CRA), the short posterior ciliary arteries (PCA), and the ophthalmic artery (OA). All patients were examined before and after injection on day 1‑7 and 30 day during the 3‑month follow up period.Results: Before intravitreal injection Vsyst was decreased in short PCA (p<0.05), RI in CRA and in short PCA significantly increased in comparison with normal index in same vessels. The peak systolic velocity in OA, in CRA and in short PCA was not significantly changed. After second injection resistance index in CRA and in short PCA was normalized.Conclusion: There was not impairment of ocular blood flow in retinal and choroidal after monthly intravitreal injection of ranibizumab during the 3‑month follow up period.